Femoral Versus Nonfemoral Subclavian/Carotid Arterial Access Route for Transcatheter Aortic Valve Replacement: A Systematic Review and Meta‐Analysis - Laurent Faroux; Lucia Junquera; Siamak Mohammadi; David Del Val; Guillem Muntané‐Carol; Alberto Alperi; Dimitri Kalavrouziotis; Eric Dumont; Jean‐Michel Paradis; Robert Delarochellière; Josep Rodés‐Cabau (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2020)
Background Some concerns remain regarding the safety of transcarotid and transsubclavian approaches for transcatheter aortic valve replacement. We aimed to compare the risk of 30‐day complications and death in transcarotid/transsubclavian versus transfemoral transcatheter aortic valve replacement recipients. Methods and Results Data from 20 studies, including 79 426 patients (16 studies) and 3992 patients (4 studies) for the evaluation of the unadjusted and adjusted impact of the arterial approach were sourced, respectively. The use of a transcarotid/transsubclavian approach was associated with an increased risk of stroke when using unadjusted data (risk ratio [RR], 2.28; 95% CI, 1.90–2.72) as well as adjusted data (odds ratio [OR], 1.53; 95% CI, 1.05–2.22). The pooled results deriving from unadjusted data showed an increased risk of 30‐day death (RR, 1.46; 95% CI, 1.22–1.74) and bleeding (RR, 1.53; 95% CI, 1.18–1.97) in patients receiving transcatheter aortic valve replacement through a transcarotid/transsubclavian access (compared with the transfemoral group), but the associations between the arterial access and death (OR, 1.22; 95% CI, 0.89–1.69), bleeding (OR, 1.05; 95% CI, 0.68–1.61) were no longer significant when using adjusted data. No significant effect of the arterial access on vascular complication was observed in unadjusted (RR, 0.84; 95% CI, 0.66–1.06) and adjusted (OR, 0.79; 95% CI, 0.53–1.17) analyses. Conclusions Transcarotid and transsubclavian approaches for transcatheter aortic valve replacement were associated with an increased risk of stroke compared with the transfemoral approach. However, these nonfemoral arterial alternative accesses were not associated with an increased risk of 30‐day death, bleeding, or vascular complication when taking into account the confounding factors.